Factors that Influence Decision Making through the Application of Management Accounting Information Systems - Fadjar, Achmad; Nisjar Sardjudin, Karhi (International Journal of Psychosocial Rehabilitation, 2020)
The role of management accounting information system (MAIS) is very important in providing the information needed by managers for decision-making in a company. To achieve the success of implementation of MAIS requires management commitment and organizational culture. The purposes of this research are to analyze the influence of management commitment and organizational culture on the implementation of MAIS and its implications for decision-making. The method employed in this research is the descriptive and explanatory research one. The type of data used is the primary one, and the measurement scale used is the ordinal one. The data collection is conducted using survey technique through the instrument of questionnaires that are distributed to the three-four-and-five-star hotels in the province of West Java, and the respondents involved are line managers. The validity and reliability are tested for the questionnaires that have been collected. Then the data are converted within the interval scale. The data analysis is conducted both descriptively and inferentially with the assistance of the weighted mean score and path analysis statistics, respectively. The results of the research indicate both management commitment and organizational culture influence managers’ decision-making through the application of MAIS.